Analysis of Structural Aspects in the Novel Laut Bercerita by Leila S. Chudori - Khariza, Ayatus Dona; Muarifin, Moch.; Puspitoningrum, Encil (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
Human life does not escape from a creation. All the results of human creativity are called works. One of the most popular works is literature. Novels are included in the type of prose. Novels contain complex stories accompanied by depictions of characters that reflect real life so that novels can become quality reading material that contains various values of life that can be learned for readers. Novels are created through the process of imagination and creativity of the author in expressing ideas and views on things in the real world. A story in a novel can be composed because of the elements that build and create a coherent and structured whole. Intrinsic elements are useful to glue or link into a unified story. This research uses a structural approach to examine intrinsic elements in the form of themes consisting of major and minor themes, characters consisting of main and companion characters, characterization consisting of protagonists and antagonists, and internal and external conflicts in the novel. This research is included in qualitative descriptive research with data presentation in description sentences related to the findings.